Preference of tertiary care centres over peripheral health centres for routine NCD care: a cross-sectional study in hypertensive and diabetic individuals - Majgi, Sumanth Maliikarjuna; S., Swathi Kamal (International Journal Of Community Medicine And Public Health, 2020)
Background: Although there is a program for non-communicable diseases (NCD) control and facilities for their management at the peripheral health centres (PHCs), many patients visit tertiary health care centres (THCs), spending 25 -35% of their income for health care on a long term basis for routine NCD care. Objective of the study was to identify the reasons for these patients not visiting the nearest PHC facility and to estimate the money and the time spent by the patients visiting the THC for such unwarranted visits. Methods: This cross-sectional study was conducted on 207 patients with diabetes mellitus and/or hypertension at Medicine OPD at K. R. Hospital, Mysuru, THC and the patients were interviewed with the help of a questionnaire. Results: All 207 (100%) were routine NCD care. 44% of the participants stated that they felt satisfied with services at THC while 5.8% had no specific reason to state for choosing to seek NCD care at THCs. Also, many patients are not aware of the facilities available at the PHC and hence visit THCs, even for routine NCD care. The average overall expense incurred per person per visit to the THC was approximately Rs. 640. The costs incurred on transportation and on drugs were statistically significant. The major contributing component for the total expense incurred was found to be the money spent on the drugs. Conclusions: Strengthening health systems are recommended by improvement in availability and prescription of essential NCD drugs along with creating awareness about various government schemes that offer good financial coverage for the poor households.